A comparative study between calcium alginate fibre and gelatin sponge in control of hemorrhage in extraction sites in cats - Achacoso, Karl; Llado, Margarette; Serraon, Antolin (Adviser).
This research paper aims to determine the efficiency of calcium alginate fibre (Kaltostat) and gelatin sponge (Spongostan) in the control of post-extraction bleeding. 15 female adult cats were selected. Properly sedated and anesthetized the upper and lower premolars immediately beside the molars of the right side were extracted. Gelatin sponge was packed in the upper premolar socket while calcium alginate fibre was packed in the lower premolar socket. The contralateral teeth were also extracted and served as control. The time required to achieve hemostasis in each socket was recorded. The data was then subjected to statistical analysis. Results show that calcium alginate fibre is significantly more efficient than gelatin sponge in controlling post-extraction bleeding.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Calcium alginate fibre (Kaltostat).; Gelatin sponge (Spongostan).